The intricacy and delicacy in the historical development of Arabic language - Yaacob, Solehah@Nik Najah Fadilah (Dewan Bahasa dan Pustaka, 2016)
The main linguistic tradition was created by the Arabs since in the seventh century, ending in the nineteenth century with the reception of Western linguistics. The issues in Arabic linguistics which recapitulated on some linguistic speculation were developed by Western linguists. Some scholars were of the view that there was a hidden Greek transmission into Arabic linguistics and terminology which were subsequently borrowed by traditional Arab scholars who started to describe their own language scientifically (academically). However, the speculation above has been rejected by some Muslim scholars who believe that the purity of Arabic linguistics such as the theory of Arabic syntax is totally free from any foreign influence. This book highlights some views of Muslim scholars on the originality of Arabic linguistics by traditional Arab grammarians who focus more on the grammatical approach in applying the method. The chapters of this book are arranged according to the historical and corpus linguistic chronology. The first six chapters discuss the history of Semitic languages with the opening chapter gives a brief history of Semitic languages of which the Arabic language is believed to be the root. The remaining five chapters deal with various Arabic traditional linguistic elements such as syntax, morphology, semantic, declension and logic focus on the analogical approach method as the main ideas in exploring Arabic grammar. The author believes that the strength of this book is on the discussion of the issues. She cannot deny that there are many scholars, either linguists or historians who have covered the above mentioned topic. However, based on her observation, deliberations or discussions from Muslim scholars` point of views hailed from non-Arab region (Southeast Asia Region) do not exist.